Pete the Cat and the missing cupcakes - Dean, Kim, 1969-; Dean, James, 1957- (New York, NY : Harper, an imprint of HarperCollins Publishers, 2016)
When Pete the Cat and his friends get ready for a cupcake party, where Pete is performing with his band, they discover some of the cupcakes have gone missing and must find out who is taking them.
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Cupcakes -- Juvenile fiction; Cats -- Juvenile fiction; Animals -- Juvenile fiction; Friendship -- Juvenile fiction